2020
DOI: 10.1186/s12885-020-06891-5
|View full text |Cite
|
Sign up to set email alerts
|

Cancer incidence attributable to tuberculosis in 2015: global, regional, and national estimates

Abstract: Background: Tuberculosis is associated with increased risk of cancer. However, the impact of tuberculosis on global cancer burden is unknown. Methods: We performed random-effects meta-analyses and meta-regressions of studies reporting the association between tuberculosis and cancer risks by searching PubMed, Web of Science, Embase, Cochrane library, and CINAHL from inception to 1 June 2019. Population attributable fractions (PAFs) of cancer incidence attributable to tuberculosis were calculated using relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 31 publications
(36 reference statements)
2
18
0
Order By: Relevance
“…In low prevalence regions, on the other hand, many had much older patient collectives 3,11,24 . Reasons therefore typically are a much older general population and, as also shown in the present study, higher rates of immunosuppressive diseases or medications in low prevalence regions 25 . Although cancer or immunosuppressive medication are the major reasons for immunosuppression in low prevalence regions, 26 mostly affecting elderly patients, simultaneous infection with HIV is the main reason for immunosuppressive conditions in high prevalence regions, 27,28 which often affects a younger part of the population.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…In low prevalence regions, on the other hand, many had much older patient collectives 3,11,24 . Reasons therefore typically are a much older general population and, as also shown in the present study, higher rates of immunosuppressive diseases or medications in low prevalence regions 25 . Although cancer or immunosuppressive medication are the major reasons for immunosuppression in low prevalence regions, 26 mostly affecting elderly patients, simultaneous infection with HIV is the main reason for immunosuppressive conditions in high prevalence regions, 27,28 which often affects a younger part of the population.…”
Section: Discussionsupporting
confidence: 69%
“…3,11,24 Reasons therefore typically are a much older general population and, as also shown in the present study, higher rates of immunosuppressive diseases or medications in low prevalence regions. 25 Although cancer or immunosuppressive medication are the major reasons for immunosuppression in low prevalence regions, 26 mostly affecting elderly patients, simultaneous infection with HIV is the main reason for immunosuppressive conditions in high prevalence regions, 27,28 which often affects a younger part of the population. Therefore, two groups account for the majority of newly diagnosed TB patients in low prevalence countries: Younger, otherwise healthy patients who migrated from regions with high TB burden and older patients who might have had an infection decades ago, when the prevalence of TB was higher in all regions, and now suffer from an activation of the infection caused by an immunosuppression.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a systematic review showed that TB infection was associated with haematological malignancies, including HL, NHL, and leukaemia. 26 Ageing is a risk factor for NHL transformation, particularly DLBCL, MZBL, and Burkitt lymphoma, in TB patients. Case-control studies support the indication that TB infection is a risk factor for the incidence of DLBCL.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term pathogen-induced chronic inflammatory stimulation will increase the risk of cancer. Helicobacter pylori, hepatitis virus, human papillomavirus and Epstein-Barr virus are common susceptible carcinogens (9). The continuous inflammatory stimulation and tissue damage/ repair caused by MTB infection are also important reasons for the development of LC.…”
Section: Mechanisms Of Chronic Inflammation Elicited By Mtb Infection In Tumorigenesismentioning
confidence: 99%
“…As an important factor in causing tumors, carcinogenic infections are responsible for about 15.4% (2.2 million) of 14 million new cases of cancer in 2012 (8,9). And with the improvement of the treatment of LC, the wide application of immunotherapy and the prolonged survival of LC patients, the co-existence of TB and LC is becoming more common in clinical practice, especially in developing countries with high burden of TB.…”
Section: Introductionmentioning
confidence: 99%